The Adoption of Found Child According to Islamic Law and Law No. 3 of 2006 on Religious Courts in the Perspective of Maqasid Al-Shari'ah - Siti Muniroh; Khoiruddin Nasution (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2021)
Islam is a religion that regulates everything in the life of Muslims. No exception in the case of adoption, the jurisdiction of the court up to the adoption of a minor. in the case of child adoption. Today, Islam applies limitations in some matters, such as the prohibition of lineage, the establishment of non-mahram relationships to the issue of inheritance and guardianship. In addition to that field, there is the authority of the judge in the Religious Court to be ijtihad to determine the best decision for the child of the findings as the extent of its authority is based on Law No. 3 of 2006 on Religious Justice. The purpose of this study is to analyze how the legal impact on the adoption status of the findings based on the rationale maqasidus syar'i and its relevance to the development of Islamic law. Research methods use the study of literature through its sources of reference through primary law, both derived from religious sources and from positive legal sources that apply in Indonesia. In addition, the researcher used jurisprudence from the relevant judicial decisions used.The results of this research are (1) through the approach of maqasid al shari'ah doruriyah that children (including children of discovery) must be protected their rights, both their right to life (an nafs) and their intellect (al aql), the right of lineage, religion, as well as paying attention to his rights, including his right to obtain the obligatory will/right of inheritance from the parents who raised him (al maal), (2) The legal impact is, the child is found as a person, he is an orphan so the religious treatment is the same as an orphan. While the adopted child then the legal status can be assessed through recognition by the adoptive parents such as the child of guardianship, then the adopted child has the right to be guarded by his adoptive parents due to the absence of a lineage guardian. (3) While the relevance to the development of Islamic law is that in maintenance (other than the issue of lineage and inheritance), then the child has the same protection and education status of both adoptive parents. There is a need for efforts from various related parties to prioritize the benefits to protect from unwanted things and save the lives of children.